Case Study on Varma Management of Global Development Delay - Anpuchelvi, S.; Sritharan, G.; Ganesan, S. (Global Academic Research Institute Colombo, Sri Lanka, 2024)
Background: Developmental delay refers to a slower rate of development in a child across four primary domains: motor, mental, social, and communication skills, compared to peers of the same age. When multiple domains are affected, the condition is termed 'Global Developmental Delay'. Purpose: This case study focuses on the management of children with global developmental delay. Materials and Methods: Data was collected from the inpatient department of a tertiary care Herbal Health care Centre, Kokuvil, Jaffna. Subjects were assessed for growth and development using parameters such as anthropometry and developmental milestones (gross motor, fine motor, social, and language skills). The study utilized various multidimensional Siddha & Varma treatment modalities for the selected case. Results and Conclusion: The subjects showed considerable improvements in the domains of gross motor and fine motor skills. Siddha & Varma therapeutic procedures can be effectively utilized in the management of developmental delay.
Keywords: Siddha & Varma treatment; Global developmental delay